(untitled) (Stavební obzor - Civil Engineering Journal, 2023)
In this paper, the practical engineering of a 420 m PC continuous beam bridge is taken as the research object, and an external prestressing reinforcement method is proposed to reinforce the damaged and cracked girder. The paper is to study the structural performance of PC continuous beam bridge before and after reinforcement. The heavy vehicle loading test of reinforced PC continuous beam bridge was carried out. A total of three test spans were selected, and each test span selected seven deflection test section and a strain test section. The corresponding finite element model was established and verified by the test results. Finally, it was concluded in this study that the external prestressing reinforcement method has a good effect on improving the loading capacity and overall performance of damaged bridges.